Toxic Epidermal Necrolysis in a Boy with Dravet Syndrome: Clinical Case - Aset Kh. Ibisheva; Lechi R. Kagaev; Linda V.-M. Dzhabrailova; Malika M. Gadueva; Iman Sh. Masayeva; Madina A. Denilkhanova (Педиатрическая фармакология)
Background. Toxic epidermal necrolysis (TEN) is significant public health issue as it is associated with high mortality. Clinical case description. The authors have described the case of TEN in a boy with Dravet syndrome. Data on TEN course and real prevalence in children around the world is limited due to its rare incidence. Conclusion. Successful experience in TEN management has been presented.